Physical Assaults assessment concerning their pattern, severity & bone of contention, in rural areas of Punjab - Nadir Ali, Sadaf Sajid, Noreen Farid, Naveed Ahmad, Asma Javed, Naveed Ahmad, Asma Javed, Usama Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The rural areas of Punjab have a very high prevalence of physical assault due to illiteracy, pride of cast system, related to agricultural land disputes, illegal breaches in violating the watering system of their crops, political motives of landlords in their area, and social issues related to marriages, love affairs, and illegal interference into the privacy of others. Aim: To analyze different forms of physical assaults related to their pattern, severity, and reasons behind these physical assaults keeping in view their medico-legal aspects. Methods: The data of physical assaults in medico-legal cases were collected from the peripheral rural areas of Faisalabad, Sargodha and Mianwali on specifically designed Performa. The cases were selected from these districts reported in Causality & Accident departments of the district and tertiary care Hospitals during one year June 2020 to May 2021. The inclusion criteria were based on non-probability with random sampling in this retrospective study. In total 200 cases were selected for this study. Association with demographic parameters like age, sex, type of weapon used, the pattern of injury. Results: Physical Assaults had a direct association with male predominance; the age of 20 to 30 years of age, blunt weapons especially fists, kicks, and daggers, wooden sticks were used for offense as determined by the findings in this study. Various social reasons related to cast & clan system, disputes of agricultural land, family issues related to inheritance, illiteracy, pride of cast system, domestic violence, illegal breaches in violating the watering system of their crops, political motives of landlords in their area and social issues related to marriages, love affairs and illegal interference into the privacy of others, were the main bone of contentions. Conclusions: Different variety of weapons used in the rural setting. Males as predominant participants of assault suggest a socially active status of men in the rural setup of Punjab where male dominance is evident. The feudal system of landlords main responsible for social injustice and exploitation of the low class, is determined in this study. There need reforms through social literacy, justice provision for all, reforms in medico legal reporting and social awareness of human rights.